Exploring campus mental health support for international graduate students in Arizona - Collins Ezea; April Petillo (Journal of International Students, 2026)
International students face elevated mental health risks linked to acculturative stress, academic pressure, sociocultural adjustment, and structural barriers in higher education. Although these challenges are recognized, less attention has been given to how universities design and deliver support for this population. This study used a descriptive phenomenological design to examine perspectives on international graduate students’ mental health across Arizona universities. In-depth semi-structured interviews were conducted with counseling professionals and international student services staff at Northern Arizona University, with perspectives from the University of Arizona and Arizona State University. Data were analyzed using reflexive thematic analysis. Findings showed that students’ mental health challenges were cumulative and linked to cultural, academic, and social transitions. Cultural beliefs shaped help-seeking, with stigma, self-reliance, and fear of burdening others contributing to delayed use of formal services. Participants also described services as uneven in accessibility and cultural responsiveness, while staff often served as gatekeepers to care